Effect of Various Canopy Shapes on the Drag Coefficient of Pickup Trucks - Anwar, Khairil; Fadly, Muhammad Syaiful; Hermanto, Muhammad Wahyu (Universitas Negeri Malang, 2025)
The aerodynamic performance of light commercial vehicles, such as the Suzuki Carry, plays a crucial role in their fuel economy and road stability. One typical add-on, a canopy, often changes that airflow and, as a result, alters the drag acting on the vehicle. In this study, three different canopy shapes, flat, curved, and triangular, were examined to understand how each one affects the drag coefficient (Cd). To investigate this, both wind tunnel trials and CFD runs were conducted to track the airflow and measure any changes in drag with greater detail. For reference, the exact vehicle without a canopy was used as the base for comparison. From what has been observed, it is clear that adding a canopy tends to increase drag compared to leaving the cargo bed open. Of the three shapes tested, the flat canopy proved to be the most effective in increasing Cd, especially at moderate speeds. At around 80 km/h, for example, it pushed drag up by just over 11.063%. On the other hand, the curved canopy yielded the best result, adding only about 2.071% at 60 km/h. Flow images from the CFD runs showed that the flat and triangular designs disrupted the airflow more significantly, resulting in greater flow separation and larger wakes behind the truck. In contrast, the curved canopy seemed to keep the air closer to the surface, leaving less turbulence in its wake.